Students’ Digital Reading Habits for Digital Academic Text and Their Achievement - Putra, Hadi; Ahmad, Erza; Umamah, Atik (IJET (Indonesian Journal of English Teaching), 2023)
Abstract. The role of digital media is much useful for contributing to creating reading habits through the benefit of technology. Technology has grown up these days, the young generation is living a life in the modern area, where they could get their education everywhere not bound to a classroom. That’s the way the promoting of to create a literate society or reading habit in this modern era is might be important for EFL to study more easily with creating a literate society through reading cause reading is the identification of the symbols and the association of appropriate meaning with them. This study describe about what is the level of students’ digital reading habits for academic text with descriptive quantitative and the correlation between students’ habits in reading digital academic text and their achievement, is there any correlation or not. 95 students who have done with their reading material for academic text in 4th semester, only 39 students were include for this research. 31 item questionnaire was distributed to obtain data about students’ reading habit in digital academic text and their achievements. For the second instrument is based from the final course reading exam. The first result in student’s reading habits in digital academic text have an average result habits in reading or low habits in reading based on the SPSS calculation for the descriptive statistic, it means there are some other aspects of student’s reading habits in this private university by comparing for the previous study. Afterward the researcher analyze the data after collecting it. The data shows that students’ reading habits in digital academic text don’t affect on student achievement, it means that there is no significant correlation between the students’ reading habits in digital academic text and their achievement in the 4th semester at the private university of Malang.